2021
DOI: 10.3847/1538-4357/abca3c
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Reference AGN Monitoring Experiment (FRAMEx). I. Jumping Out of the Plane with the VLBA

Abstract: We present the first results from the Fundamental Reference active galactic nucleus (AGN) Monitoring Experiment, an observational campaign dedicated to understanding the physical processes that affect the apparent positions and morphologies of AGNs. In this work, we obtained simultaneous Swift X-ray Telescope and Very Long Baseline Array (VLBA) radio observations for a snapshot campaign of 25 local AGNs that form a volume-complete sample with hard X-ray (14–195 keV) luminosities above 1042 erg s−1, out to a di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 82 publications
3
49
0
Order By: Relevance
“…While jetted AGN and low/hard XRBs clearly lie on the same FPBHA (Merloni et al 2003;Falcke et al 2004), Gültekin et al (2019), by including radio-active high-/soft-state XRBs, cannot rule out that the latter and Seyferts are inconsistent with the FP made up of low-/hard-state XRBs and LINERs. Furthermore, Fischer et al (2021) have recently shown that, Seyferts, once resolved with the VLBI on sub-parsec scales, can have corresponding L core upper limits that are systematically below the predictions from the FPBHA. The tension with the analogies between stellar-mass BHs and active SMBHs probably rests on attempting to use the optical class to set the association.…”
Section: Low-luminosity Agn and Disc-jet Couplingmentioning
confidence: 99%
“…While jetted AGN and low/hard XRBs clearly lie on the same FPBHA (Merloni et al 2003;Falcke et al 2004), Gültekin et al (2019), by including radio-active high-/soft-state XRBs, cannot rule out that the latter and Seyferts are inconsistent with the FP made up of low-/hard-state XRBs and LINERs. Furthermore, Fischer et al (2021) have recently shown that, Seyferts, once resolved with the VLBI on sub-parsec scales, can have corresponding L core upper limits that are systematically below the predictions from the FPBHA. The tension with the analogies between stellar-mass BHs and active SMBHs probably rests on attempting to use the optical class to set the association.…”
Section: Low-luminosity Agn and Disc-jet Couplingmentioning
confidence: 99%
“…However, this means-again-that the plane is no more probing the disk-jet coupling. Many other works underlined these and other flaws [see (Chiaberge, 2007;Foschini, 2014;Saikia et al, 2018;Berton et al, 2019a;Fischer et al, 2021), just to cite a few]. Nevertheless, these types of fundamental planes are still luring researchers, because of their ease.…”
Section: Scaling Lawsmentioning
confidence: 99%
“…The "fundamental plane of black hole activity" for black holes with low accretion rates (Merloni et al 2003;Falcke et al 2004;Fischer et al 2020) encompasses stellar-mass black hole X-ray binaries and AGN, and enables one to estimate the black hole mass based upon the nuclear radio emission, L R = νL ν erg s −1 (at 5 GHz), and the unabsorbed nuclear X-ray luminosity, L X erg s −1 (at 0.5-10 keV). Although, it is noted that some AGN are X-ray luminous but radio silent (Radcliffe et al 2021).…”
Section: X-ray Luminosities: the Fundamental Plane Of Black Hole Acti...mentioning
confidence: 99%